Perancangan dan Pengembangan Platform Kursus Coding Berbasis Digital untuk Mendukung Pembelajaran Teknologi - Daffarizqy Prastowiyono; Muhammad Adzka; R. Bramaditya Ario Wirawisesa; Wien Kuntari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Mastering technology is essential in the digital age, particularly for building programming skills. However, a lack of access to good learning materials and adaptable learning systems remains a major challenge. This research intends to create a digital-based coding course platform that effectively and efficiently supports technical learning. To provide the best learning experience, the platform includes different features such as organized learning materials, hands-on exercises, and automated evaluations. The development methods used include analyzing user needs and implementing modern web technologies. Testing results indicate that the platform can enhance users' grasp of coding concepts and encourage them to keep learning. The platform is anticipated to offer innovative solutions for technology education for various groups, from students to professionals.